Synergistic Saccharification, and Direct Fermentation to Ethanol, of Amorphous Cellulose by Use of an Engineered Yeast Strain Codisplaying Three Types of Cellulolytic Enzyme - Fujita, Yasuya (American Society for Microbiology, 2004)
A whole-cell biocatalyst with the ability to induce synergistic and sequential cellulose-degradation reaction was constructed through codisplay of three types of cellulolytic enzyme on the cell surface of the yeast Saccharomyces cerevisiae. When a cell surface display system based on α-agglutinin was used, Trichoderma reesei endoglucanase II and cellobiohydrolase II and Aspergillus aculeatus β-glucosidase 1 were simultaneously codisplayed as individual fusion proteins with the C-terminal-half region of α-agglutinin. Codisplay of the three enzymes on the cell surface was confirmed by observation of immunofluorescence-labeled cells with a fluorescence microscope. A yeast strain codisplaying endoglucanase II and cellobiohydrolase II showed significantly higher hydrolytic activity with amorphous cellulose (phosphoric acid-swollen cellulose) than one displaying only endoglucanase II, and its main product was cellobiose; codisplay of β-glucosidase 1, endoglucanase II, and cellobiohydrolase II enabled the yeast strain to directly produce ethanol from the amorphous cellulose (which a yeast strain codisplaying β-glucosidase 1 and endoglucanase II could not), with a yield of approximately 3 g per liter from 10 g per liter within 40 h. The yield (in grams of ethanol produced per gram of carbohydrate consumed) was 0.45 g/g, which corresponds to 88.5% of the theoretical yield. This indicates that simultaneous and synergistic saccharification and fermentation of amorphous cellulose to ethanol can be efficiently accomplished using a yeast strain codisplaying the three cellulolytic enzymes.